2022
DOI: 10.1186/s12936-022-04394-1
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity of Plasmodium falciparum merozoite surface protein 1 and 2 and multiplicity of infections in western Ethiopia following effective malaria interventions

Abstract: Background Genetic diversity of malaria parasites can inform the intensity of transmission and poses a major threat to malaria control and elimination interventions. Characterization of the genetic diversity would provide essential information about the ongoing control efforts. This study aimed to explore allelic polymorphism of merozoite surface protein 1 (msp1) and merozoite surface protein 2 (msp2) to determine the genetic diversity and multiplicity of Plasmodium falciparum infections circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 56 publications
(66 reference statements)
1
11
1
Order By: Relevance
“…In high malaria transmission areas of Equatorial Guinea in West Africa, these same alleles had substantially higher frequencies of 96.07%, 96.09%, and 70.78%, respectively [ 22 ]. The frequency of the msp-2 gene I/C 3D7 allele ranged from 15.9% to 98.3% in Ethiopia [ 19 , 79 ], while the FC27 allele frequency ranged from 10.3% in Ethiopia [ 84 ] to 98.9% in high malaria transmission areas in Benin [ 36 ]. Meanwhile, the frequency of glurp ranged from 39.53% among symptomatic individuals in a high malaria transmission setting in Nigeria [ 68 ] to 97.6% among severe malaria cases living in malaria-moderate areas in Uganda [ 74 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In high malaria transmission areas of Equatorial Guinea in West Africa, these same alleles had substantially higher frequencies of 96.07%, 96.09%, and 70.78%, respectively [ 22 ]. The frequency of the msp-2 gene I/C 3D7 allele ranged from 15.9% to 98.3% in Ethiopia [ 19 , 79 ], while the FC27 allele frequency ranged from 10.3% in Ethiopia [ 84 ] to 98.9% in high malaria transmission areas in Benin [ 36 ]. Meanwhile, the frequency of glurp ranged from 39.53% among symptomatic individuals in a high malaria transmission setting in Nigeria [ 68 ] to 97.6% among severe malaria cases living in malaria-moderate areas in Uganda [ 74 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean values of parasite genetic diversity and MOI are higher in areas with high malaria transmission intensity [ 16 , 17 ] and lower in those with low transmission intensity [ 18 ]. Additionally, mean Plasmodium falciparum genetic diversity and MOI apparently decreased following the suppression of Plasmodium falciparum transmission intensity in areas of Ethiopia [ 19 ] and Senegal [ 20 ]. In other studies, mean values of Plasmodium falciparum genetic diversity were higher among individuals with symptomatic infections [ 21 , 22 ] and lower in those with asymptomatic infections [ 23 ], and were inversely correlated with parasite density and patient age [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to higher rates of transmission, complex polygenomic malaria parasite infections are common in Africa, although this was not the case for infections from Ethiopia, which had also been shown previously with SNPs to be the least complex but most divergent from the rest of continent (Amambua-Ngwa et al 2019). This is not surprising as malaria transmission in Ethiopia is extremely low, with highly clonal infections and significant geographic barriers to spatial gene flow with the rest of Africa (Tessema et al 2020; Abera et al 2021; Tadele et al 2022). Consequently, isolates from Ethiopia also had relatively higher index of association, a measure of LD, probably driven by the higher inbreeding and lower infection complexity (Tadele et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as malaria transmission in Ethiopia is extremely low, with highly clonal infections and significant geographic barriers to spatial gene flow with the rest of Africa (Tessema et al 2020; Abera et al 2021; Tadele et al 2022). Consequently, isolates from Ethiopia also had relatively higher index of association, a measure of LD, probably driven by the higher inbreeding and lower infection complexity (Tadele et al 2022). The overall LD, which is a function of the level of recombination, also correlated with those determined by SNPs, further confirming the usefulness of this set of microsatellites loci for population genetic studies of P. falciparum in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there were considerable heterogeneity across the included studies in this meta-analysis (I 2 = 92.69%, p-value < 0.001). The highest weight among studies was observed from studies conducted by Mohammed, Kassa et al 2), Tadele, Jaiteh et al (30). The included studies were assessed for potential publication bias using Egger's test.…”
Section: Pooled Prevalence Of Allelic Family Of Msp-1 and Msp-2 Gene ...mentioning
confidence: 99%